Things from the flood - Stålenhag, Simon (Skybound Books/Gallery Books, 2020)
"Welcome back to the Loop. In 1954, the Swedish government ordered the construction of the world's largest particle accelerator in the pastoral countryside of Mälaröarna. The local population called this marvel of technology The Loop and celebrated its completion. But Mälaröarna and the world would never be the same. Infused with strange machines and unfathomable creatures, Things from the Flood is transcendent look at technology that will stay with you long after you turn the final page."--